PARTISIPASI PEREMPUAN ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH DALAM PEMBENTUKAN PERATURAN DAERAH DI KOTA SEMARANG - DWI ESTY WIDYASTUTI, Amiek Soemarmi, Retno Saraswati (Diponegoro Law Journal, 2013)
Regional House of Representatives (Parliament) is the representative body for realizing the sovereignty of the people in the area. The function of Parliament as an institution representative of all the people in the region is a vehicle for the implementation of democracy in the area that serves as an element of the regional administration.The presence of women legislators of Semarang are limited, making the existence of a large role and influence policy making in parliament should be able to do them. In the context of equality, women should also have had a hand in the formulation of policy, but if the quality of women legislators could not cope with the swift struggle of equality, this will certainly be a bad thing for the struggle.Because, let alone equality policy, a line of women's issues rarely touched. It means that the presence of women legislators is questionable. On this basis, the authors take the title "PARTICIPATION OF WOMEN MEMBERS OF THE HOUSE OF REPRESENTATIVES IN THE FORMATION OF THE REGULATIONS IN THE CITY SEMARANG", with the question of how the participation of women members of parliament in the formation of local regulations in the city of Semarang, any obstacles encountered in drafting local regulations, and how efforts to completion.Writing this law using Empirical juridical approach, namely Descriptive analytical research specifications, the data used are secondary data and primary data, methods of data analysis using qualitative analysis methods, methods of presenting data through primary data and secondary data obtained through research.Based on these results it can be concluded that the participation of women members of the House of Representatives in the establishment of the Regional District Regulation in Semarang was pretty good, but still need to increase the quality, considering from the beginning until now there has been no local regulations pertaining on women's interests. In the process pembentukkannya, encountered some obstacles, among other differences, time constraints, lack of knowledge and understanding of the duties and functions of Parliament, particularly the lack of experience and knowledge related to the field of assignment parliament. However, these obstacles can be overcome by efforts to develop Human Resource (HR) and increase pofesionalisme and experience.